2015
DOI: 10.17116/jnevro201511571141-145
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and Parkinson’s disease: mechanisms and perspectives of treatment

Abstract: Процесс образования свободных радикалов относит-ся к универсальным механизмам жизнедеятельности лю-бой живой клетки. Их основным источником является процесс трансформации кислорода в митохондриях. По-ступающий в клетку кислород подвергается полному вос-становлению до воды. Однако в процессе аэробного мета-болизма при неполном восстановлении кислорода в каче-стве промежуточных продуктов образуются свободные радикалы (СР). Они представляют собой различные по атомному составу химические вещества, общей особенно-с… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In addition, oxidative stress-induced apoptosis participates in the development of nervous system diseases, whereas intervention with antioxidants reduces the apoptosis via inhibiting the generation of ROS and thereby resulting in neuroprotective effects (19). Multiple studies have reported that ROS contributes to the apoptosis-associated mechanism of MPP + -mediated neurotoxicity (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress-induced apoptosis participates in the development of nervous system diseases, whereas intervention with antioxidants reduces the apoptosis via inhibiting the generation of ROS and thereby resulting in neuroprotective effects (19). Multiple studies have reported that ROS contributes to the apoptosis-associated mechanism of MPP + -mediated neurotoxicity (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, the activity of antioxidant systems decreases with age, contributing to the age-related decline in the resistance of dopaminergic nigrostriatal neurons to pro-Parkinsonian factors and the progressive increase in PD patients. The concept of oxidative stress in the pathochemical mechanisms of neuronal damage in PD defines an avenue for pathogenetic therapy with antioxidants [ 43 ]. The high content of paramagnetic centers in melanins enables them to deactivate radicals due to their high electron absorption capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced oxidative stress and neuroinflammation [5,6] are involved in the pathogenesis of PD. We then explored whether SIP can relieve PD during repressing oxidative stress and inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The main pathological features of PD are the deposition of Lewy bodies and loss of dopaminergic neurons in substantia nigra pars compacta (SNc) [24]. Enhanced oxidative stress and inflammatory responses [5,6], protein misfolding and aggregation [7], and dysfunction of the ubiquitin-proteasome system [8] are involved in the pathogenesis of PD, but the exact mechanism leading to degeneration of dopaminergic neurons remains unclear. Current drugs for the treatment of PD are mainly based on improving dopamine concentration in the brain or activating dopamine receptors to improve the motor symptoms of PD [9].…”
Section: Introductionmentioning
confidence: 99%